Characterizing the fatigue resistance of multiple modified asphalts using time sweep test, LAS test and elastic recovery test. (7th March 2022) - Yan, Chuanqi; Yuan, Linxin; Yu, Xiaotao; Ji, Shuzhen; Zhou, Zhengfeng
Highlights: The fatigue performances of multiple representative modified asphalts are evaluated. Three testing methods, namely time sweep, elastic recovery and LAS are compared. Failure criterion should be carefully selected regarding modified asphalts. LAS shows a better correlation with elastic recovery at increasing strain levels. Elastic recovery may be a promising indicator of asphalt/mixture fatigue life. Abstract: The fatigue cracking due to the repeated traffic loading is one of the main distresses that reduces the performance and service life of the asphalt pavements. The asphalt phase of asphalt mixture is the most critical for resisting fatigue damage, and thus it must be carefully evaluated for fatigue performance. Previous studies mainly focused on a limited range of asphalt materials while the applications of multiple new kinds of modified asphalts have surged in recent years. This study aimed to evaluate the fatigue resistance of 7 representative modified asphalts, including the linear SBS polymer modified asphalt, crumb rubber modified asphalt, terminal blend (TB) rubberized asphalt, EVA modified asphalt, Rock asphalt modified asphalt and bio oil modified asphalt. Three tests (times sweep test, LAS test and Elastic recovery test) and four different failure criterions are evaluated. Results suggested that elastomeric modified asphalts show the best fatigue performance, followed by non-elastomeric modified asphalts and plain asphalt. Elastomeric modified asphalts appear to show better fatigue resistance at higher strain level conditions. Also, the fatigue life of LAS test shows a good correlation with the elastic recovery, and the correlation improves with increasing strain levels. This suggests that elastic recovery could be a promising indicator for asphalt/mixture fatigue life characterization.